The Relationship Between Use of the Internet and Traditional Information Sources - Satoshi Kitamura (SAGE Open, 2013)
This study examines how the spread of the Internet has affected Japanese people’s information acquisition from traditional media or via traditional information channels. In particular, this study focuses on displacement and complementary effects and on devices for Internet access. Using representative data from Japan ( N = 1,179), the results show that Internet use via mobile phone has complementary effects on information acquisition from traditional media, while Internet use via personal computers does not. In addition, the results show that Internet use via personal computers has a displacement effect on information acquisition from radio. These findings are discussed with regard to communication means, social contexts, and media interfaces.